A study on dynamic trim optimization of VLCC oil tanker in wind and waves. (1st June 2022) - Li, Jiandong; Duan, Wenyang; Chen, Jikang; Ma, Shan; Zhang, Yahui
Abstract: Ships have become the main means of transportation in the world trade. With paying more attention to global warming problems, the Greenhouse Gas (GHG) emission reduction of ships has been extensively studied. Trim optimization is taken as a GHG reduction technology. Considering trim optimization of calm water resistance is energy-saving, but it cannot always be the best state in practice affected by wind and waves. The difficulty on trim optimization in wind and waves is the calculation of added resistance. On account of the high-cost and long-period, the experimental method and Computational Fluid Dynamics (CFD) method are ill-suited for trim optimization. In this paper, high-efficiency and high-accuracy Taylor Expansion Boundary Element Method (TEBEM) and ITTC two-parameter spectrum are used for calculating added resistance in regular and irregular waves respectively. Wind load is estimated by empirical formula. Trim optimization of a 300K-ton VLCC oil tanker on a typical route is studied. Compared with calm water trim optimization, it is found that dynamic trim optimization in wind and waves can save about 949.3 kg fuel and the fuel saving potential is about 0.04%, based on the average sea states over the whole route. Therefore, dynamic trim optimization during navigation is more beneficial. Highlights: Taylor Expansion Boundary Element Method is used to solve added resistance of VLCC oil tanker at different trim angles. The sea states of a typical route of VLCC oil tanker is analyzed statistically. Dynamic trim optimization of VLCC oil tanker can be more beneficial to reduce CO2 at different sea states on a typical route.